(untitled) (Fiep Bulletin - online, 2012)
Currently a stream of current thinking includes the idea of environmental sustainability in order to produce the leastimpact on the planet, gaining visibility in the media and the behavior of the population. In this context, I emphasize the action of the"Cycle Route," an alternative reality before this materialistic / capitalist who we are as beings. This practice is not defined bynumber, age, gender, race, nationality, creed, political or religious, cultural, works by the will and decision of individuals who cometogether by affinities, route, and perform independent activities ecological and socio-cultural forms of itinerant , preferably on footor by bicycle, short, long or indefinite duration. The purpose of this paper is to present, discuss and relate the Cycleway Projectwith the discipline of agroecology and the bicycle as a cultural element endowed with multiple meanings, and also explain aboutthe need for this practice to the world in the context of environmental sustainability. The union between the bike and Agroecologytranslates into actions of the bike path as a viable path to restoring the environment degraded by human activities fromenvironmental sustainability. Before praising a few people hold the financial power and image, we can look at attitudes like thisand realize that there is any solution to this inequality and the solutions are simpler than we think, feasible to the points of doingwell in and around that surrounds us.